Afectos, Emociones Y Sentimientos De Los Estudiantes Panameños Hacia La Matemática Y Su Aprendizaje - Lebrija, Analinnette; Gutiérrez, Jaime; Alvarado, Mayra Trejos (European Scientific Journal, ESJ, 2017)
We report partial results of an action-dynamic research, of descriptive type, conducted by a learning community that organizes and structures the educational process according to events that occur during a school year; it is based on the constructivist method and the solution of real problems, primarily. It is centered on beliefs about affect, emotions and feelings of Panamanian seventh grade students towards the learning of Mathematics, related to Math Science, Math Class, the Learning of Math and Learning Strategies. The learning community has considered the influence that these factors have on the process of knowledge construction of vital importance. Some important results are as follows. In relation to Science and the motivation towards it, the intervention changed the percentages, for example, from 70.8% to 100.0%, as far as the taste for the class that receives 72.4% were interested in studying Mathematics, 93.5% of the students said at the end of the school year that all students can learn mathematics. Initially, 89.3% believed to know learning strategies, the percentage in this criterion decreased, this was due to the researchers’ intervention better understood their methodology. From these partial analyses we can observe evidence for the possibilities and challenges of change in the teaching and learning of Math. These results are part of a larger research whose general objective is to design, develop and evaluate a program for teaching and learning Mathematics, based on the modification of negative learning believes from students, and a model for applying daily-life problem-solving strategies, structured on the pre-media curriculum of Panama, that are not part of this article.